Lady and the Tramp (Disney Movie Collection: A Special Disney Storybook Series, 2015)
Cocker spaniel Lady has the perfect life with her loving owners. When her life is turned upside down by the arrival of a new baby and some unwelcome guests, Lady decides to run away. Lady soon meets streetwise Tramp, who is obviously from the wrong side of town, but has a good heart. With friends like these, life on the streets can't be that bad - can it? Enjoy this exclusive large size Disney movie storybook, featuring beautifully illustrated pages fans can treasure for years to come